(untitled) (CIPEEX, 2025)
BACKGROUND: Accidents involving venomous animals have increased in Brazil, affecting urban, semi-urban, and predominantly rural areas1. Spiders rank as the second most reported group, following scorpions2. In Anápolis, Goiás, 341 cases recorded from 2020 to 2025 underscore the local significance of these incidents, which can constitute medical emergencies with risks of morbidity and mortality, necessitating epidemiological analysis to inform prevention and healthcare strategies3. OBJECTIVE: To analyze the epidemiological profile of spider bite accidents in Anápolis, focusing on time to medical care, victim’s educational level, and clinical outcomes. METHODS: This is an observational, descriptive, and retrospective study, based on SINAN/DATASUS data regarding spider accidents in Anápolis, Goiás (2020–2025), examining the relationship between educational level, time to seek medical care and outcomes of spider bite cases. RESULTS: Of the 341 cases, 9.7% did not report educational level, 1.5% were illiterate, 25.8% had incomplete primary education, 8.2% complete primary, 10% incomplete secondary, 31.7% complete secondary, 2.9% incomplete higher education, and 10.3% complete higher education4. This distribution across education levels was heterogeneous, but without a clear predominance. Regardless of time to medical care, 340 cases resulted in recovery. The sole reported death occurred after 24 hours post-accident5. CONCLUSION: Although rural areas have higher incidence of venomous animal accidents and lower educational levels, care-seeking was not proportionally higher in this group1,6. Geographic and socioeconomic barriers may limit timely access to healthcare in rural settings7,8. Time to medical care did not significantly influence clinical outcomes, except that it is relevant to highlight that the only death recorded from spider accidents was associated with care provided more than 24 hours after the incident, indicating a correlation between delayed treatment and more severe outcomes.